The role of active mRNA–ribosome dynamics and closing constriction in daughter chromosome separation in Escherichia coli - Chathuddasie I. Amarasinghe; Mu-Hung Chang; Jaana Männik; Scott T. Retterer; Maxim O. Lavrentovich; Jaan Männik (Proceedings of the National Academy of Sciences, 2025)
The mechanisms by which two sister chromosomes separate and partition into daughter cells in bacteria remain poorly understood. A recent theoretical model has proposed that out-of-equilibrium central dogma reactions involving mRNA and ribosomes play a significant role in this process. Here, we test this idea in the Escherichia coli model system using high-throughput fluorescence microscopy in microfluidic devices. We compare our experimental observations with predictions from a reaction–diffusion model that includes central dogma-related reactions and excluded volume interactions between ribosomal subunits, polysomes, and chromosomal DNA. Our results show that the nonequilibrium reactions of ribosomes cause them to aggregate at the midcell, and this process facilitates the separation of the two daughter chromosomes. However, the observed effects are weaker in live cells than our one-dimensional reaction–diffusion model predicts. Rather than relying solely on active mRNA–ribosome dynamics, our data suggest that the closing division septum via steric interactions and potentially entropic forces between two DNA strands coupled to cell elongation act as additional mechanisms to ensure faithful partitioning of the nucleoids to two daughter cells.